2015
DOI: 10.1155/2015/417846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adult Male Circumcision on Premature Ejaculation: Results from a Prospective Study in China

Abstract: The purpose of this study is to investigate the effects of adult male circumcision on premature ejaculation (PE). Therefore, between December 2009 and March 2014, a total of 575 circumcised men and 623 uncircumcised men (control group) were evaluated. Detailed evaluations (including circumcision and control groups) on PE were conducted before circumcision and at the 3-, 6-, 9-, and 12-month follow-up visits after circumcision. Self-estimated intravaginal ejaculatory latency time (IELT), Patient-Reported Outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 29 publications
3
31
0
2
Order By: Relevance
“…Circumcision has been proposed as a permanent treatment for PE caused by hypersensitivity of the glans. In a recent prospective cohort, patients post‐circumcision at 1‐year follow up had significantly higher IELT, sexual satisfaction and subjective control over ejaculation when compared with uncircumcised controls . However, multiple systematic reviews published 2 years prior found that the rate of PE or other sexual dysfunctions were not significantly different between circumcised and uncircumcised men in the general population .…”
Section: Future Developmentsmentioning
confidence: 93%
See 4 more Smart Citations
“…Circumcision has been proposed as a permanent treatment for PE caused by hypersensitivity of the glans. In a recent prospective cohort, patients post‐circumcision at 1‐year follow up had significantly higher IELT, sexual satisfaction and subjective control over ejaculation when compared with uncircumcised controls . However, multiple systematic reviews published 2 years prior found that the rate of PE or other sexual dysfunctions were not significantly different between circumcised and uncircumcised men in the general population .…”
Section: Future Developmentsmentioning
confidence: 93%
“…Resiniferatoxin has been shown to improve IELT in patients with PE . Strangely, resiniferatoxin was significantly more effective in patients with redundant prepuce, further complicating the relationship between circumcision and PE . Unfortunately, in patients without redundant prepuce, the treatment was not more effective than a placebo, but the study population was particularly small .…”
Section: Future Developmentsmentioning
confidence: 97%
See 3 more Smart Citations